(untitled) (Journal of Global Accounting, 2023)
The study investigates the effect of firm characteristics on the earnings management of listed conglomerate firms in Nigeria. The explanatory variable of firm characteristics is measured in terms of firm size (FSZ) and firm age (AGE) The dependent variable of earnings management is measured in terms of discretionary accrual (DA). The ex-post facto research design was applied. The population and sample size of the study comprised five (5) conglomerate firms listed on the Nigerian Exchange Group (NGX). The secondary data were obtained from the audited financial statements of the selected firms from 2012 to 2021. The results of the Ordinary Least Square regression analysis revealed that firm size has a statistically insignificant effect on earnings management as measured in terms of discretionary accrual of the pooled conglomerate firms in Nigeria, at neither a 5% nor a 1% significant level. The results obtained from the OLS regression model revealed that firm age has a statistically significant effect on earnings management as measured in terms of discretionary accrual of the pooled conglomerate firms in Nigeria at a 5% significant level. The study recommends that investors in listed conglomerate firms in Nigeria should always be on the lookout for the potential for more real activity earnings management before arriving at their investment decisions.